Optimizing High School English Language Learning: The Impact of Modern Learning Apps and Technology Platforms - Aulia Hanifah Qomar (Intensive Journal, 2024)
The aim of this research is to gain a thorough understanding of how the most recent information technology has affected English language learning in the present, as well as to determine what kinds of platforms and applications are thought to be most useful for helping students improve their command of the language. Additionally, a detailed analysis of the English language learning platform's implementation in Muhammadiyah schools in the Metro will be included in this research. A survey design is used in this study as a quantitative research methodology. The participants in this survey research will be drawn from MTs Muhammadiyah Metro, SMP Muhammadiyah Metro, and SMP Muhammadiyah Ahmad Dahlan, three Muhammadiyah secondary schools located in Metro City. Once the pre-survey is completed, samples will be chosen and the methodology will be decided upon by researchers at the schools and madrasas that have been identified as the research population. The result of the study shows that Female research participants make up the majority (90.09%) of the sample, while male subjects make up just 9.01%), according to the findings of the demographic analysis of the study data. The demographic information provided above indicates that there may be gender biases or trends in the research that could affect the analysis's findings or the dynamics of student participation in the use of technology in the classroom. Moreover, the research focus was at a certain grade level or educational unit stage in high school, as the bulk of research subjects (90.08%) were 17 years old.